Cloud based social interactive media application - Ankit Agarwal (2012)
This report discusses and documents the work done by the author over a year, in partial fulfillment of the requirements for the degree of Bachelor of Computer Engineering of the Nanyang Technological University. Author has precisely summarized his detailed workings in the development of the social interactive media application over cloud, in this report. This report mostly comprises of the Mobile Application Development over the Android OS (2.3.3). The main focus here is to enhance the traditional TV watching experience, by increasing retention through social interaction, y providing a chatting experience while consuming the video real time or leveraging on existing social networking sites. The report is organized such that it defines the Software Development Life Cycle (SDLC) for the entire Application Development process. Author in the introductory chapter gives the motivation, background and the general ‘layman’ insight to the project idea. Subsequently the report dwells into more focused content to explain thoroughly the development process employed by the author. Author then describes his viewpoint on the existing literature, available to him, and critically analyses each one of them, in order to opt for the most optimal design. Then from requirements, activity, system design to object design, author caters to all of these aspects of the SDLC in full detail and with the help of standard UML diagrams represents and defines them. Implementing the proposed design into a functional application is the next step. And then the author concludes the SDLC by testing his application on a real setup under ‘unfamiliar conditions’. Further, after being convinced by his efforts in the development of the application, in the concluding chapter author describes the future of such an application in the coming years, and the wide pool of opportunities, a research of this high potential promises to offer to the society.